The logical structure of time according to the chapter on the Schematism - Caimi, Mario Pedro Miguel (2012)
Usually, when studying schematism we devote almost exclusive attention to the study of the modifications that the categories suffer when combined with time. Instead, we have focused our attention on the determinations that time receives when combined with the categories. Departing from the definition of the transcendental schemata as "determinations of time", an attempt is made to establish the various determinations that time receives from each one of the categories, as these perform the determination of time in schematism. The categories of quantity allow us to think of time as a series of homogeneous unities; the categories of quality show each instant of time as a receptacle able to receive the different intensities (degrees) of the real; the categories of relation establish a rule-dependent order on the flow of time; finally, the categories of modality determine the whole of time forming a collective unity that gathers or embraces each one of the instants of time preserving its specificity (its individual features).